2021
DOI: 10.1038/s41467-021-24582-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the contribution of Neanderthal introgression to the heritability of complex traits

Abstract: Eurasians have ~2% Neanderthal ancestry, but we lack a comprehensive understanding of the genome-wide influence of Neanderthal introgression on modern human diseases and traits. Here, we quantify the contribution of introgressed alleles to the heritability of more than 400 diverse traits. We show that genomic regions in which detectable Neanderthal ancestry remains are depleted of heritability for all traits considered, except those related to skin and hair. Introgressed variants themselves are also depleted f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 86 publications
(144 reference statements)
7
68
1
Order By: Relevance
“…Our findings that introgressed variants are not enriched in psychiatric and neurological diagnostic categories are in line with a recent broad analysis that showed very limited associations of Neandertal variants with disease in modern humans beyond dermatological or immune-mediated disorders (38). The enrichment of associations with traits such as chronotype, pain, alcohol and tobacco use rather than diagnostic disease categories may thus reflect adaptations.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings that introgressed variants are not enriched in psychiatric and neurological diagnostic categories are in line with a recent broad analysis that showed very limited associations of Neandertal variants with disease in modern humans beyond dermatological or immune-mediated disorders (38). The enrichment of associations with traits such as chronotype, pain, alcohol and tobacco use rather than diagnostic disease categories may thus reflect adaptations.…”
Section: Discussionsupporting
confidence: 90%
“…They also presented a signal of enrichment across traits for human-specific promoters. Further, another recent study showed that variants introgressed from Neanderthals and shared across multiple Neanderthal populations are enriched in heritability for some traits (17). However, to our knowledge, this study is the first to analyze the role of a range of human-gained genetic and epigenetic sequence elements originating at different times in shaping complex traits and disease evolution (Fig.…”
Section: Main Textmentioning
confidence: 85%
“…They also presented a signal of enrichment across traits for human-specific promoters. Further, another recent study showed that variants introgressed from Neanderthals and shared across multiple Neanderthal populations are enriched in heritability for some traits ( 17 ).…”
Section: Main Textmentioning
confidence: 99%
“…However, beyond general agreement that introgressed archaic DNA has mainly been deleterious and actively removed from coding sequences and conserved non-coding elements [8,[12][13][14], the actual phenotypic consequences of this variation are not well understood. Several lines of evidence highlight associations between archaic DNA and risk for disease traits, including autoimmune diseases [8,15,16], or with traits of possible evolutionary advantage for early non-Africans [17,18]. For example, Neanderthal variants within immune genes and immune-related cis-regulatory elements (CREs) have been associated with differential responses to viral infections among present-day Europeans [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…First, we still lack a detailed characterisation of global levels of human genetic diversity, vital to identifying differential archaic hominin contributions across modern populations [21,22]. Because Denisovan DNA is not present in the genomes of modern Europeans, which make up the vast diversity of biomedical genetics cohorts, it has been impossible to link them to phenotype, unlike segregating Neanderthal variants [16,23]. Second, and more challenging, most of these alleles lie within non-coding sequences where, despite their acknowledged contributions to human evolutionary history [24,25], an understanding of their actual biological functions remains elusive.…”
Section: Introductionmentioning
confidence: 99%